2007
DOI: 10.1002/ijc.23250
|View full text |Cite
|
Sign up to set email alerts
|

CS‐706, a novel cyclooxygenase‐2 selective inhibitor, prolonged the survival of tumor‐bearing mice when treated alone or in combination with anti‐tumor chemotherapeutic agents

Abstract: The potent chemopreventive activity of cyclooxygenase-2 (COX-2) inhibitors has been demonstrated in a number of preclinical studies, but their potency in antitumor activity is still in dispute. In this report, we demonstrate the potent antitumor activity of a novel COX-2 inhibitor, CS-706 in mouse colorectal adenocarcinoma colon 26 tumor-bearing mice treated with or without antitumor chemotherapeutic agents. Daily oral administration of CS-706 at doses of 3-100 mg/kg from the day of tumor inoculation (Day 0) i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 32 publications
0
16
0
Order By: Relevance
“…COX-2 expression correlates with VEGF levels in patient tumor samples and COX-2 inhibition can modulate VEGF production (27, 34). VEGF levels in plasma and tumor samples collected from mice tumor-bearing mice were measured by ELISA.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…COX-2 expression correlates with VEGF levels in patient tumor samples and COX-2 inhibition can modulate VEGF production (27, 34). VEGF levels in plasma and tumor samples collected from mice tumor-bearing mice were measured by ELISA.…”
Section: Resultsmentioning
confidence: 99%
“…Apricoxib is a novel, selective COX-2 inhibitor currently in phase II studies for NSCLC and pancreatic cancer. Apricoxib has showed significant antitumor effects in xenograft models of lung and colorectal cancer and seems more potent than previous COX-2 inhibitors (23, 27, 28). In this study, we characterized the baseline expression and activity of EGFR and COX-2 in commonly employed pancreatic cancer cell lines as well as functional responses to inhibition of each pathway.…”
Section: Introductionmentioning
confidence: 98%
“…In a phase 2 trial, celecoxib treatment improved overall survival in patients who suffered from COX-2-positive esophageal and gastroesophageal junction cancer (11). In colorectal adenocarcinoma, CS-706, a novel COX-2 selective inhibitor, was demonstrated to have potent life-prolonging activity in tumor-bearing mice (12). In ovarian cancer, Xin et al (13) identified that meloxicam, categorized as a selective COX-2 inhibitor, prolonged survival in vivo when administered alone.…”
Section: Discussionmentioning
confidence: 99%
“…Few studies have also concluded that COX-1 inhibitors are able to reduce tumor growth by decreasing cell proliferation and accelerating apoptosis (6,10). Additionally, COX-2 inhibitors have demonstrated potent life-prolonging effects in patients with esophageal and gastroesophageal junction cancer (11) and in various animal models of cancer (12,13).…”
Section: Introductionmentioning
confidence: 99%
“…14, 15 Clinical studies demonstrated potent analgesic activity 16, 17 and preclinical studies demonstrated good pharmacokinetics, pharmacodynamics and gastrointestinal tolerability. 18 As an anticancer agent, preclinical studies demonstrated efficacy in biliary tract cancer models 19 and colorectal carcinoma, 20 and Recamp et al 21 recently reported a Phase I trial of 1 in combination with erlotinib in lung cancer.…”
mentioning
confidence: 99%